A meta-analysis on the predictive validity of English language proficiency assessments for college admissions. (April 2023) - Ihlenfeldt, Samuel Dale; Rios, Joseph A.
For institutions where English is the primary language of instruction, English assessments for admissions such as the Test of English as a Foreign Language (TOEFL) and International English Language Testing System (IELTS) give admissions decision-makers a sense of a student's skills in academic English. Despite this explicit purpose, these exams have also been used for the practice of predicting academic success. In this study, we meta-analytically synthesized 132 effect sizes from 32 studies containing validity evidence of academic English assessments to determine whether different assessments (a) predicted academic success (as measured by grade point average [GPA]) and (b) did so comparably. Overall, assessments had a weak positive correlation with academic achievement ( r  = .231, p  < .001). Additionally, no significant differences were found in the predictive power of the IELTS and TOEFL exams. No moderators were significant, indicating that these findings held true across school type, school level, and publication type. Although significant, the overall correlation was low; thus, practitioners are cautioned from using standardized English-language proficiency test scores in isolation in lieu of a holistic application review during the admissions process.